Respuesta :
Answer:
x = 3 ± √5
Step-by-step explanation:
Step 1: Square root both sides
√(x - 3)² = ±√5
x - 3 = ±√5
Step 2: Add 3 to both sides
x = 3 ± √5
x = 0.763932, 5.23607
If your equation is 2(x - 3) = 5, then:
Step 1: Distribute
2x - 6 = 5
Step 2: Add 6 on both sides
2x = 11
Step 3: Divide both sides by 2
x = 11/2
Answer:
x = 5.5
Step-by-step explanation:
Let's look at our problem: (x – 3)2 = 5
Ok, first things first we need to multiply the parentheses first! If we break it up it looks like this:
x*2 - 3*2 =5
Now we see that we have:
2x - 6 = 5
We now add the like terms which are 6 and 5. We add 6 on both sides to eliminate 6 from the right side and move it to the left:
2x - 6 = 5
+6 +6
We now get:
2x = 11
Now we divide by two on both sides so we find out what x alone is:
[tex]\frac{2x}{2}[/tex] = [tex]\frac{11}{2}[/tex]
Now we have our answer!
x = 5.5
Alright everyone, give yourself a pat on the back because that was a toughie!